Dermoscopic Features of CD8-Positive Solitary Pagetoid Reticulosis on the Left Leg - Reiko Suzaki; Ken Kobayashi; Sumiko Ishizaki; Mariko Fujibayashi; Masaru Tanaka (Dermatology Research and Practice)
Solitary pagetoid reticulosis, also known as Woringer-Kolopp disease, is a rare subtype of cutaneous T-cell lymphoma. The typical clinical presentation is a solitary, localized psoriasiform or hyperkeratotic plaque or tumor located on the extremities. It primarily affects middle-aged males. Because the clinical features of pagetoid reticulosis are indistinctive, pagetoid reticulosis may progress for years before accurate diagnosis. We reported a 57-year-old Japanese woman who presented with a 1-year history of a solitary erythematous plaque on the left leg. Dermoscopic features simulated Bowen's disease showing dotted and glomerular vessels, whitish scaly areas, and a broad negative network. Dermoscopic features of pagetoid reticulosis have never been reported. We have discussed the diagnostic significance of the observed dermoscopic findings.